Yellowstone's Old Faithful Geyser Shut Down by a Severe Thirteenth Century Drought. Issue 20 (17th October 2020) - Hurwitz, Shaul; King, John C.; Pederson, Gregory T.; Martin, Justin T.; Damby, David E.; Manga, Michael; Hungerford, Jefferson D. G.; Peek, Sara
Abstract: To characterize eruption activity of the iconic Old Faithful Geyser in Yellowstone National Park over past centuries, we obtained 41 new radiocarbon dates of mineralized wood preserved in the mound of silica that precipitated from erupted waters. Trees do not grow on active geyser mounds, implying that trees grew on the Old Faithful Geyser mound during a protracted period of eruption quiescence. Rooted stumps and root crowns located on higher parts of the mound are evidence that at the time of tree growth, the geyser mound closely resembled its current appearance. The range of calibrated radiocarbon dates (1233–1362 CE) is coincident with a series of severe multidecadal regional droughts toward the end of the Medieval Climate Anomaly, prior to the onset of the Little Ice Age. Climate models project increasingly severe droughts by mid‐21st century, suggesting that geyser eruptions could become less frequent or completely cease. Plain Language Summary: The rarity of natural geysers reflects the special conditions needed for their formation, including an abundant supply of water. Therefore, severe droughts of extended duration could have led to large variations in the frequency and intensity of geyser eruptions. To characterize potential changes in eruption activity of the iconic Old Faithful Geyser in Yellowstone National Park over past centuries, we collected mineralized wood samples from its mound and used radiocarbon to date when these trees grew. Because trees do not live on active geyser mounds, we infer that the trees grew during a protracted period without eruptions. The dated fossil trees are from the thirteenth and fourteenth centuries during a time with severe multidecadal droughts in the region. Because climate models forecast increasingly severe droughts by mid‐21st century, geyser eruptions could become less frequent or completely cease. Key Points: Yellowstone's Old Faithful Geyser stopped erupting for many decades in response to severe multidecadal regional droughts in the thirteenth century Wood is preserved for over 650 years because silica‐rich alkaline waters deposit amorphous opal on cellular films Because climate models project increasingly severe droughts by mid‐21st century, eruptions could become less frequent or completely cease